Bond strength and development length of steel bar in unconfined self-consolidating concrete. (15th January 2017) - Mousavi, S.S.; Dehestani, M.; Mousavi, K.K.
Highlights: Existing equations for normal concrete are not efficient and applicable for SCC. New models proposed for predicting interfacial properties of steel bar–SCC interface. Accuracy of new models was checked by a supplementary experimental program. Bar diameter, cover, type and contents of aggregates and cement were considered. Lower development lengths for steel bar in SCC than NC were observed. Abstract: There are no specific models for evaluating bond strength and development length of steel bar in unconfined self-consolidating concrete (SCC). Existing equations for steel bar embedded in normal concrete are not efficient and applicable for SCC. So, it is essential to introduce more precise and efficient models. In this study, pull out tests of referenced literatures are used to present new predicting equations. Unlike existing equations, proposed models demonstrate acceptable fit with the database. Also, in order to evaluate the accuracy of the proposed models, direct pull out tests are performed in this study. The results of experimental test are in good agreement with those obtained by proposed new models.